2018
DOI: 10.3171/2017.6.jns163188
|View full text |Cite
|
Sign up to set email alerts
|

Is the chiasm-pituitary corridor size important for achieving gross-total resection during endonasal endoscopic resection of craniopharyngiomas?

Abstract: OBJECTIVE Craniopharyngiomas arise from the pituitary stalk, and in adults they are generally located posterior to the chiasm extending up into the third ventricle. The extended endonasal approach (EEA) can provide an ideal corridor between the bottom of the optic chiasm and the top of the pituitary gland (chiasm-pituitary corridor [CPC]) for their removal. A narrow CPC in patients with a prefixed chiasm and a large tumor extending up and behind the chiasm has been considered a contraindication to EEA, with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 39 publications
0
15
1
Order By: Relevance
“…7,12,16,21,40 Furthermore, it has been shown that a narrow surgical window between the pituitary gland and optic chiasm does not preclude a ventral approach. 64 Recurrent tumors present significant challenges when treated via either approach, but with ESBS it appears that the extent of resection (87.0%) and visual outcomes (76.5% improvement) remain similar, and major complication rates are comparable to first-time rates (3.6% first time vs 0.0% recurrent), but with a higher rate of new postoperative diabetes insipidus for reoperations (47.0% first time vs 80.0% recurrent). 21 Prior radiation, however, continues to make further surgery more complicated, regardless of the approach.…”
Section: Data From 2012 To 2017mentioning
confidence: 96%
“…7,12,16,21,40 Furthermore, it has been shown that a narrow surgical window between the pituitary gland and optic chiasm does not preclude a ventral approach. 64 Recurrent tumors present significant challenges when treated via either approach, but with ESBS it appears that the extent of resection (87.0%) and visual outcomes (76.5% improvement) remain similar, and major complication rates are comparable to first-time rates (3.6% first time vs 0.0% recurrent), but with a higher rate of new postoperative diabetes insipidus for reoperations (47.0% first time vs 80.0% recurrent). 21 Prior radiation, however, continues to make further surgery more complicated, regardless of the approach.…”
Section: Data From 2012 To 2017mentioning
confidence: 96%
“…They may present as entirely solid or with an associated cystic component and may frequently engulf neurovascular structures in the interpeduncular and suprasellar cisterns. In adults, they arise most commonly posterior to the chiasm and extend posteriorly into the third ventricle [138]. The papillary histopathological type account for at least one-quarter of cases in the adult age group and this finding translates into more solid lesions with fewer calcifications [4,198], a homogeneous contrast enhancement and a thickened pituitary stalk [193].…”
Section: Evidencementioning
confidence: 99%
“…16 On occasion, sacrifice of a descending branch of the superior hypophyseal artery is necessary to gain appropriate surgical access to the interval between chiasm and pituitary gland, also known as the chiasm-pituitary corridor. 24 Great care is taken to preserve branches of the superior hypophyseal artery to the chiasm, which can be swept north following transection of the descending branch.…”
Section: Surgical Techniquementioning
confidence: 99%
“…Tumor-related expansion frequently enlarges the interval between the chiasm, which is often displaced anteriorly, and the infundibular recess. 23,24 In larger tumors, the inferior margin of the third ventricle is commonly displaced inferiorly, where it can be stretched to a thin translucent membrane. Access to the tumor capsule can be obtained via an incision in the thin membrane occupying the region between anteriorly displaced chiasm and stalk.…”
Section: Surgical Techniquementioning
confidence: 99%